Introduction to developmental psychology - Slater, Alan.; Bremner, J. Gavin (Malden, MA : Blackwell Publishing, 2003)
This is an account of human development from conception to adolescence. It is organised chronologically and also thematically, and the chapters written by international experts. It is designed for a broad range of readers, and in particular those with little previous exposure to psychology.
Includes bibliographical references and index.
Keywords: Developmental psychology